Polar ozone depletion: Current status - Henderson, G. S.; McConnell, J. C.; Beagley, S. R.; Evans, W. F. J. (Canadian Journal of Physics, 1991)
Rapid springtime depletion of column ozone (O 3 ) is observed over the Antarctic during the austral spring. A much weaker springtime depletion is observed in the Arctic region. This depletion results from a complex chemical mechanism that involves the catalytic destruction of stratospheric ozone by chlorine. The chemical mechanism appears to operate between ~12–25 km in the colder regions of the polar winter vortices. During the polar night heterogeneous chemical reactions occur on the surface of polar stratospheric clouds that convert relatively inert reservoir Cl species such as HCl to active Cl species. These clouds form when temperatures drop below about 197 K and are ubiquitous throughout the polar winter region. At polar sunrise the reactive Cl species are photolysed, liberating large quantities of free Cl that subsequently catalytically destroys O 3 with a mechanism involving the formation of the Cl 2 O 2 dimer. The magnitude of the spring depletion is much greater in the Antarctic relative to the Arctic owing to the greater stability and longer duration of the southern polar vortex. Breakup of the intense high-latitude vortices in late (Antarctic) or early (Arctic) spring results in infilling of the ozone holes but adversely affects midlatitude ozone levels by diluting them with O 3 -depleted, ClO-rich high-latitude air. The magnitude of the Antarctic ozone depletion has been increasing since 1979 and its current depletion in October 1990 amounts to 60%. The increase in the size of the depletion is anticorrelated with increasing anthropogenic chlorofluorocarbon (CFCs) release. Adherence to the revised Montréal Protocol should result in a reduction of stratospheric halogen levels with subsequent amelioration of polar ozone depletion but the time constant for the atmosphere to return to pre-CFC levels is ~60–100 years.